2012
DOI: 10.1186/1471-2334-12-206
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between effects of carbapenems and flomoxef in treating nosocomial hemodialysis access-related bacteremia secondary to extended spectrum beta-lactamase producing klebsiella pneumoniaein patients on maintenance hemodialysis

Abstract: BackgroundHemodialysis (HD) patients are susceptible to extended spectrum beta-lactamase (ESBL)-producing bacterial infections. Because the optimal treatment and clinical significance of ESBL-producing Klebsiella pneumoniae (ESBL-Kp) HD access-related bacteremia remain unclear, we conducted this retrospective study to determine the clinical outcomes of patients treated with either flomoxef or a carbapenem.MethodsThe eligibility criterion was fistula or graft- or catheter- related ESBL-Kp bacteremia in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
2
25
4
Order By: Relevance
“…The MIC of flomoxef was Յ1 g/ml. (21,22). Flomoxef treatment was associated with higher mortality than that of the controls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The MIC of flomoxef was Յ1 g/ml. (21,22). Flomoxef treatment was associated with higher mortality than that of the controls.…”
Section: Discussionmentioning
confidence: 90%
“…To date, 5 reports have evaluated the efficacy of cephamycins for the treatment of infections ESBL-producing members of the Enterobacteriaceae (8,(19)(20)(21)(22). All of these single-center retrospective studies included a small number of patients and a control group comprised of patients receiving carbapenem.…”
Section: Discussionmentioning
confidence: 99%
“…Existing observational studies comparing cephamycins and carbapenems are plagued by the inherent limitations of observational studies-most notably confounding by indication-as well as small sample sizes (Table 2) [15][16][17][18][19][20]. Only 1 of these studies showed improved outcomes among ESBL-infected patients treated with carbapenems compared with cephamycins, while the others could not detect differences [18] (Table 3). Optimal dosing regimens and achievable target attainment for various cephamycin minimum inhibitory concentrations (MICs) need to be explored [21].…”
Section: Cephamycinsmentioning
confidence: 86%
“…Two small observational studies evaluated flomoxef in comparison with carbapenems with contradictory results. 118,94 Also, a retrospective cohort study showed similar efficacy of cefmetazole and carbapenems in patients with pyelonephritis due to ESBL-producers (cure rate, 9/10 vs 12/12, respectively). 119 Regarding BLBLI, a post hoc analysis of prospective cohorts of patients with bloodstream infections due to ESBL-producing E. coli showed similar results for empirical or definitive therapy with in vitro active BLBLIs and carbapenems after controlling for confounders 120 ; the sources of BSI in this study were mostly urinary and biliary tracts, and high doses were used (amoxicillin/clavulanic acid: 2/0.2 g/8 h; piperacillin/tazobactam, 4/0.5 g/6 h).…”
Section: Which Carbapenem Should Be Used For Esbl-producers?mentioning
confidence: 86%